Cognitive grammar : a basic introduction - Langacker, Ronald W. (Oxford ; New York : Oxford University Press, 2008)
This book fills a long standing need for a basic introduction to Cognitive Grammar that is current, authoritative, comprehensive, and approachable. It presents a synthesis that draws together and refines the descriptive and theoretical notions developed in this framework over the course of three decades. In a unified manner, it accommodates both the conceptual and the social-interactive basis of linguistic structure, as well as the need for both functional explanation and explicit structural description. Starting with the fundamentals, essential aspects of the theory are systematically laid out with concrete illustrations and careful discussion of their rationale. Among the topics surveyed are conceptual semantics, grammatical classes, grammatical constructions, the lexicon-grammar continuum characterized as assemblies of symbolic structures (form-meaning pairings), and the usage-based account of productivity, restrictions, and well-formedness. The theory's central claim - that grammar is inherently meaningful - is thereby shown to be viable. The framework is further elucidated through application to nominal structure, clause structure, and complex sentences. These are examined in broad perspective, with exemplification from English and numerous other languages. In line with the theory's general principles, they are discussed not only in terms of their structural characterization, but also their conceptual value and functional motivation. Other matters explored include discourse, the temporal dimension of language structure, and what grammar reveals about cognitive processes and the construction of our mental world.
Pt. I Preliminaries -- 1.Orientation -- 2.Conceptual Semantics -- 3.Construal -- Pt. II Fundamentals -- 4.Grammatical Classes -- 5.Major Subclasses -- 6.Constructions: General Characterization -- 7.Constructions: Descriptive Factors -- 8.Rules and Restrictions -- Pt. III Structures -- 9.Grounding -- 10.Nominal Structure -- 11.Clause Structure -- 12.Complex Sentences -- Pt. IV Frontiers -- 13.Discourse -- 14.Engaging the World.
Includes bibliographical references (p. 541-550) and index.
Keywords: Cognitive grammar